2013
DOI: 10.1007/s00259-013-2467-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of integrated whole-body [11C]choline PET/MR with PET/CT in patients with prostate cancer

Abstract: Despite a substantially later imaging time-point, the performance of simultaneous PET/MR was comparable to that of PET/CT in detecting lesions with increased [(11)C]choline uptake in patients with prostate cancer. Anatomical allocation of lesions was better with simultaneous PET/MR than with PET/CT, especially in the bone and pelvis. These promising findings suggest that [(11)C]choline PET/MR might have a diagnostic benefit compared to PET/CT in patients with prostate cancer, and now needs to be further evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 36 publications
4
58
0
3
Order By: Relevance
“…Furthermore, several studies (using 11 C-choline, 68 Ga-DOTATOC, or 18 F-FDG) have shown that PET datasets acquired by PET/MR and PET/CT are highly comparable (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies (using 11 C-choline, 68 Ga-DOTATOC, or 18 F-FDG) have shown that PET datasets acquired by PET/MR and PET/CT are highly comparable (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Specific reports evaluating PET/MRI for PCa are few. PET/CT and PET/MRI were studied with 11 C-choline in 32 men with primary or biochemically recurrent PCa (38). Lesion detection was comparable for both, but PET/MRI was better at the anatomic allocation of lesions, especially in the bone and pelvis.…”
Section: Pet/mri In Localized and Biochemically Recurrent Diseasementioning
confidence: 99%
“…The remaining 13 publications report some evidence that PET/ MRI is superior to PET/CT for characterizing primary tumours, e.g. primary bone tumours [11][12][13] or oesophageal carcinoma [14], but do not demonstrate significant advantages of whole-body MRI over whole-body PET/CT for N or M staging [15][16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…The remaining 13 publications report some evidence that PET/ MRI is superior to PET/CT for characterizing primary tumours, e.g. primary bone tumours [11][12][13] or oesophageal carcinoma [14], but do not demonstrate significant advantages of whole-body MRI over whole-body PET/CT for N or M staging [15][16][17][18][19][20][21][22][23][24].The introduction of PET/MRI was heralded as a technological breakthrough, and many expected a subsequent clinical revolution, with the newer modality vying to supersede PET/CT atop the diagnostic food chain just as the Burmese python is supplanting the American alligator in the Florida Everglades. However, none of the above-mentioned papers offers a definitive answer as to whether or not integrated and simultaneous PET/MR imaging is clinically more accurate than sequentially performed whole-body PET/CT and MRI dedicated to one body region registered in retrospect.…”
mentioning
confidence: 99%